CORMOHIPPARION SOFULARENSIS N. SP., A NEW HIPPARION SPECIES OF FROM THE LATE MIOCENE OF SOFULAR (TÜRKİYE, EARLY TUROLIAN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
In this contribution, we study the hipparion remains from the Early Turolian locality of Sofular, Türkiye. We identify the presence of a new species, Cormohipparion sofularensis, with three other taxa which we refer to Hippotherium brachypus, Hipparion dietrichi and Cremohipparion moldavicum. We compare these taxa with other Late Miocene hipparions from Iran, Türkiye, Greece, Moldova, Austria, Germany, France, Spain, Algeria and Libya, by morphologic and morphometric comparisons of crania, mandibles, maxillary and mandibular dentitions, third metacarpals and third metatarsals to further evaluate the morphological and systematic comparisons. Recently, the Sofular locality is dated radioisotopically to 8.422±0.34 Ma, correlative with early MN11 (Early Turolian) faunas in our comparisons. The Sofular hipparions record the early evolutionary radiation of hipparion lineages in the Subparatethyan Province. Our analyses further reveal that Sofular Cormohipparion sofularensis is the youngest member of the genus Cormohipparion reported from Eurasia and Africa and is found to be derived in skull morphology compared to the Late Vallesian Cormohipparion cappadocium from Yeniyaylacık, Türkiye.
Keywords: Cormohipparion; Sofular; Late Miocene; Turolian; Türkiye